How The GIG-Economy is Reshaping the World Labor Market - Heba Al-Sayed Mohamed Tolba,Ph.D. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is an attempt to analyze the phenomenon of the GIG- Economy, and explain its impact on the Global Labor market and income distribution . specially that the evolving and rising of the GIG economy over the world using the digital platforms that plays an important role in increasing the productivity and employment rate resulting from rising labor force participation and facilitate getting access to lower salaried workers from different nations , leading to more specialization and standardization of work. In GIG market , low wages workers from developing countries can earn more by engaging in similar jobs in a developed country like USA and European countries . through no barriers, and all that is needed is access to mobile/internet connection. However, Governments can deal closely with business and training centers to impart necessary additional skill for the displaced workers. As a result of the spread of gig works there is a need to invest intensively in ICT-related infrastructure such as telecommunication and internet connection.